Film Barbie sebagai Ide Penciptaan Motif Painting Tenun Sulam Bulu Garut pada Ready to Wear Deluxe - Thoyyiba, Azwa Tamara; Fitra, Annis; Kurniawan, Hadi (Style : Journal of Fashion Design, 2024)
This project aims to expand the creative repertoire of Garut embroidered woven fabric through hand painting techniques inspired by the Barbie movie. The Barbie movie is considered to contain strong elements of feminism and carries a message that inspires the younger generation, especially women. According to interviews with Garut weaving entrepreneurs, woven fabrics are still rarely favored by young people but are popular among those approximately 30 years and older. Therefore, it is hoped that the application of hand painting techniques inspired by the Barbie movie can attract the interest of the younger generation. Scenes from the Barbie movie are reinterpreted into surface designs using hand painting techniques on Garut embroidered woven fabric. The creation process of this work employs exploration, design, and realization methods.